The complete tales and poems of Edgar Allan Poe. - Poe, Edgar Allan, 1809-1849 (Vintage Books, 1975)
"One of the most original American writers, Edgar Allan Poe shaped the development of both the detective story and the science-fiction story. Some of his poems--"The Raven," "The Bells," "Annabel Lee"--Remain among the most popular in American literature. Poe's tales of the macabre still thrill readers of all ages. Here are familiar favorites like "The Purloined Letter." "The Fall of the House of Usher," and "The Murders in the Rue Morgue," together with less well-known masterpieces like "The Imp of the Perverse," "The Narrative of A. Gordon Pym" and "Ligeia," which is now recognised as one of the first science-fiction stories, a total of seventy-three tales in all, plus fifty-three poems and a generous sampling of Poe's essays, criticism and journalistic writings."--Back cover